(untitled) (Global Journal of Management and Business Research, 2015)
The global financial crisis of 2007/8 is considered to be the worst after the 1930 Great Depression. Most finance scholars argue that the crisis was a sole result of the weaknesses of the interest related traditional or conventional banking system commonly used in almost all countries in the world. Islamic finance scholars contend that the crises would have been avoided, and that will never be experienced, if the world adopted Islamic banking principles rather than clinging on to the conventional banking systems. Since Islamic financial systems are linked to, and associated with the principles of Islamic religion, other scholars maintain that the conventional systems remain the best as they accommodate all persons without being aligned to the principles of a particular religion. That aside, studies show that Islamic banking has registered a reasonable growth in asset base, especially in the Islamic nations and efforts are still there to break into the economies which are non Islamic. This study analyses the basic principles of Islamic banking in comparison with the conventional systems, and looks at the challenges and opportunities that may arise in an economy when the two systems run and operate concurrently. The paper concludes that much as the two systems can complement each other in a nation, the respective regulators must weigh the benefits and costs arising from an involvement of a new banking system in an economy. The paper further provides room for further research on the subject matter on the basis of individual country’s regulations regarding its financial systems.